Branchitis and mortality in rainbow trout Oncorhynchus mykiss exposed to iron oxidizing bacteria: Diagnostics and management in a Colorado hatchery. Issue 3 (28th March 2022) - Clift, Annie K.; Malmlov, Ashley M.; Wells, Colby L.; Cadmus, Pete; Schaffer, Paula A.
Abstract: A public trout hatchery in Colorado recorded repeat episodes of morbidity and mortality in early life stages of Rainbow Trout ( Oncorhynchus mykiss) stocks. The water source for the affected tanks is a groundwater well with a pH of 6.3 and a ferrous iron concentration of 120 µg/L. Iron oxidizing bacteria (FeOB) were suspected as the underlying cause due to insoluble red particulate matter (iron oxide precipitate) in the water, and the presence of thick red slime (biofilm) that coated tanks and pipes of the facility and adhered to gills, opercula, and fins of fry. On necropsy, gill and fin clippings from moribund fish had mats of adherent red‐orange material. Histopathology revealed severe diffuse proliferative branchitis. There was abundant debris including granular to sheath‐like and stalk‐like pigmented material within the oral and branchial chambers, intimately associated with gill filaments. A Gram preparation demonstrated florid Gram‐negative bacteria within this debris. A Perls' Prussian blue preparation revealed colocalization of abundant iron. Bacteria were identified morphologically to be of the iron oxidizing bacterial genera Gallionella and Leptothrix . This is the first known report of disease in fish associated with iron‐oxidizing bacteria. Abstract : Iron‐oxidizing bacteria (FeOB) are unique organisms that can flourish in settings of low oxygen, mild acidity, and high Fe2+. They produce orange biofilms containing iron‐oxide hydrates. FeOB colonized a groundwater well that supported a Colorado trout hatchery. The bacteria formed dense iron‐rich mats in the tanks and orobranchial chambers and were associated with severe proliferative branchitis and high morbidity and mortality. This is the first report of morbidity and mortality in fish associated with FeOB. Elimination of FeOB from contaminated systems can be very challenging; management strategies are discussed. Created with BioRender.com